Presidentialisation of electoral behavior in non election 2012 year - Peszyński, Wojciech (Political Preferences, 2013)
It is the first time when the edition of social research 'Political Preference', was carried in a year without election. It determines certain electoral attitudes, because the mass media do not influence society and voters do not take tactical decision. In consequence, the results of this research are different from the ones during real election, because these decisions have to be treated like potential ones. The author decided to continue research, which began in 2010. Therefore, electorate behavior could be compared between campaign period and 'off year election'. Apart from party leaders influencing the campaign, this article includes research results concerning television debate. Both problems are the main components of presidentialization. In the first issue prominent majority of questioned chose the party ideology as the main determinant of potential deci- sions. This conclusion is different from the previous research. This can be the main information in explaining political phenomena or processes. However, what is needed here is an appropriate distance, because in this survey the author changed answers rotation. Apart from that we have to remember about research period - 'off year election'. Although television debates have not been perma- nent component all campaigns, Polish electorate supports this idea. Over 78 per cent of researches would like to organize a debate between two main parties leaders before every elections. However, we cannot look foreword to lead this idea in the Election Code, because neither society nor politicians will insist on institutionalizing this idea.